DEVELOPMENT OF MULTICULTURALISM ON ETHNIC AND RELEGION IN INDONESIA: PERKEMBANGAN MULTIKULTURALISME PADA ETNIS DAN AGAMA DI INDONESIA - Suroyo; Bima Maulana Putra; Yuliantoro; Bedriati Ibrahim (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Multiculturalism is a phrase that refers to people's viewpoints on the world's diversity, as well as cultural policies that promote acceptance of difference. Diversity in life is an unavoidable condition, as proven by the facts mentioned above Indonesia. Hostilities had arisen across almost the whole territory of the Unitary State of the Republic of Indonesia at this time, signifying a range of differences. To attain true peace, a modern-day paradigm of ethnic and religious diversity, with a focus on religious pluralism in Indonesia, must be constructed. Using a descriptive qualitative approach and library research methodology with data collection technique, this study will collect information about books important to core intercultural education principles. Indonesian society has existed from the dawn of time. During this multicultural nation's life, our nation is engaged in a large and long-term undertaking to reestablish the spirit of oneness in diversity. Bhinneka Tunggal Ika isn't just an abstract principle here; it's also a shared respect of togetherness and pluralism. Nationality is more than a combination of bloodshed and residence. The goal of this document format, which is a documentation research technique, is to collect numerous references in the form of books, articles, documents, and other materials related to the fundamental principles of ethnic and religious multiculturalism in Indonesia. Gaining cultural understanding and ethnic literacy does not always imply that attitudes of racism, prejudice, and discrimination are abolished, and this approach undervalues the huge significance of racism. Individuality and group diversity will be stressed in educational practices, which will be vulnerable and culturally sensitive, and will consider all points of view and values to be equal. The popular belief is that the saying "Bhinneka Tunggal Ika" is only a slogan, but variety is a reality.